HAKEKAT PENDIDIK DAN PESERTA DIDIK DALAM PENDIDIKAN ISLAM - Saputra, M.Indara (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Seeing the development of more advanced education along with the times, the most important thing and one factor is to prepare educators who truly can be a role model and understand the nature of educators and learners. This is why the study of the nature of teachers and students are still attractive and deemed necessary. It should be understood that the Educators and Learners is equivalent phrase harmonious, balanced and harmonious. Relationships both are in psychiatric interdependent relationships. In parting soul, their souls are united as "duumvirate". Teachers teach and students learn in the process of educational interaction that unites them step kesatu goal of "goodness". With personal glory straighten teacher protégé dynamic that does not veer from the good